1872
DOI: 10.2307/1799577
|View full text |Cite
|
Sign up to set email alerts
|

Letter from R. B. N. Walker, F. R. G. S., on a Journey up the Ogowe River, West Africa

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…indicate that the forms differ significantly in allele frequencies at several loci, most notably in malate dehydrogenase. Secondly, there is good circumstantial evidence that the benthic and pelagic forms are reproductively isolated by having different spawning seasons and sites (Walker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…indicate that the forms differ significantly in allele frequencies at several loci, most notably in malate dehydrogenase. Secondly, there is good circumstantial evidence that the benthic and pelagic forms are reproductively isolated by having different spawning seasons and sites (Walker et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…If there is any spatial morphological variation along the loch, these functions may not be as successful in samples from other localities. While the full range of morphological measurements were not made during the early years of the ecological study, when samples were obtained from other locations around the loch (Walker et al, 1988), sufficient measurements were m a d e t o indicate close resemblance between individuals of the separate types regardless of sampling site. For example, regression of head length and eye diameter against body length were not found to be significantly different between sites.…”
Section: Discussionmentioning
confidence: 99%
“…T h e main weight of dry Bantu feces passed daily is about double that of whites, and the mean time of traversal of digesta is two to three times faster in Bantu than in whites. 31 Experimental evidence suggests that the development of polyps and cancer in the large bowel is dependnet on the fecal stream. Spjut28 has shown that 3, 2-dimethyl-4-aminodiphenyl will produce cancer in rat colons, but not in colons bypassed by colostomy.ls Furthermore, this carcinogen will not pro-(lace cancer in germ-free rats.8 There is also circumstantial evidence showing that the fecal stream influences polyp and carcinoma growth.…”
mentioning
confidence: 99%
“…More than half of patients who present with peptic ulcer haemorrhage or perforation report the recent use of these drugs. One quarter to more than half of PPU are taking NSAIDs (14,15) . Appear to be responsible most of these perforations (16) .…”
Section: Discussionmentioning
confidence: 99%